2005
DOI: 10.1007/s00702-005-0279-3
|View full text |Cite
|
Sign up to set email alerts
|

Formalin hindpaw injection induces changes in the [3H]prazosin binding to α1-adrenoceptors in specific regions of the mouse brain and spinal cord

Abstract: Involvement of the alpha1-adrenoceptor subtypes in early and late phases of formalin pain was investigated by quantitative in vitro autoradiography in the spinal cord and brain structures of CD-1 mice. Total alpha1-adrenoceptors binding (including all alpha1-adrenoceptor subtypes) was assessed with [3H]prazosin; alpha(1B)-adrenoceptor was assessed with [3H]prazosin in the presence of 10 nM WB4101 to mask remaining alpha1-adrenoceptor subtypes. Early after formalin injection the alpha1-adrenoceptors (mainly alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Quantitative autoradiography was carried out as described by Nalepa et al (2005) and Strazielle et al (1999). After decapitation, mice brains were rapidly removed, frozen, and stored on dry ice.…”
Section: Subjectsmentioning
confidence: 99%
“…Quantitative autoradiography was carried out as described by Nalepa et al (2005) and Strazielle et al (1999). After decapitation, mice brains were rapidly removed, frozen, and stored on dry ice.…”
Section: Subjectsmentioning
confidence: 99%
“…Stimulation of α 2 -adrenoceptors in the spinal dorsal horn could produce the analgesic effect through inhibition of glutamatergic synaptic transmission (Stone et al, 1998, Pan et al, 2002). Furthermore, the α 1 -adrenoceptor is present in the superficial dorsal horn of the spinal cord (Pieribone et al, 1994, Nalepa et al, 2005). We found that activation of α 1 -adrenoceptors with phenylephrine induced a dose-dependent increase in the frequency of the GABAergic sIPSCs in 76.7% of lamina Π neurons studied.…”
Section: Discussionmentioning
confidence: 99%
“…Formalin induced paw oedema [24,36] Streptococcal cell wall (SCW) arthritis [30] Collagen-induced arthritis (CIA) mouse model [31] Cell-based reporter gene assay FMLP-induced O 2 generation by poly morpho nuclear cells (PMNs). FMLP-induced adhesion of PMN of HUVEC 3-H bradykinin receptor binding [49] 3-H Substance P receptor binding Assay of PMNL chemotaxis PMNL aggregation constitutive and inducible cellular arachidonic acid metabolism Formation of leukotriene B4 in human white blood cells Formation of lipoxygenase products from 14C-arachidonic acid in human PMN Formation of eicosanoids from 14C-arachidonic acid in human platelets Bovine serum-induced inflammation [37] HRBC membrane stabilization method.…”
Section: Cell Viabilitymentioning
confidence: 99%